Widespread impact of transposable elements on the evolution of post-transcriptional regulation in the cotton genus Gossypium - Xuehan Tian; Ruipeng Wang; Zhenping Liu; Sifan Lu; Xinyuan Chen; Zeyu Zhang; Fang Liu; Hongbin Li; Xianlong Zhang; Maojun Wang (Genome Biology)
Abstract Background Transposable element (TE) expansion has long been known to mediate genome evolution and phenotypic diversity in organisms, but its impact on the evolution of post-transcriptional regulation following species divergence remains unclear. Results To address this issue, we perform long-read direct RNA sequencing, polysome profiling sequencing, and small RNA sequencing in the cotton genus Gossypium, the species of which range more than three folds in genome size. We find that TE expansion contributes to the turnover of transcription splicing sites and regulatory sequences, leading to changes in alternative splicing patterns and the expression levels of orthologous genes. We also find that TE-derived upstream open reading frames and microRNAs serve as regulatory elements mediating differences in the translation levels of orthologous genes. We further identify genes that exhibit lineage-specific divergence at the transcriptional, splicing, and translational levels, and showcase the high flexibility of gene expression regulation in the evolutionary process. Conclusions Our work highlights the significant role of TE in driving post-transcriptional regulation divergence in the cotton genus. It offers insights for deciphering the evolutionary mechanisms of cotton species and the formation of biological diversity.